Enhancing Elementary Students’ Learning Motivation through Augmented Reality-Based Educational Media: A Developmental Study - Aguscik; Fitri; Lestari, Mutiara; Fatimah (Yayasan Rumah Ilmu Professor, 2025)
In the digital era, traditional teaching methods often struggle to engage students effectively, decreasing motivation and learning outcomes. This study aims to develop and implement an Augmented Reality (AR)-based educational media to enhance students' motivation in elementary schools. The research applied a developmental approach consisting of planning, design, development, implementation, and evaluation stages. Data was collected through interviews with teachers and students, classroom observation, motivation questionnaires, and pre-and post-tests. The findings revealed a significant improvement in students' motivation, engagement, emotional involvement, and academic understanding after using the AR media. Students reported increased interest, enjoyment, and ease in grasping complex concepts. Teachers acknowledged AR's role in making learning more interactive and visually engaging. Despite initial technical challenges, students adapted quickly. This study highlights the potential of AR in transforming the learning environment and recommends broader integration of AR technology in educational settings to foster more engaging and compelling learning experiences.